Research progress on NUSAP1 and its role in digestive system neoplasms - Shangui Fu; Shangui Fu; Yuting Zhuo; Tao Yu (Frontiers in Oncology)
Nucleolar spindle-associated protein 1 (NUSAP1) is a microtubule-binding protein critical in the mitotic cell cycle. Its primary functions encompass maintaining microtubule stability, facilitating spindle assembly, regulating chromosome alignment, and modulating multiple signaling pathways. The incidence and mortality rates of digestive system neoplasms are among the highest of all malignant tumors. Therefore, identifying effective biological targets for targeted cancer control and treatment strategies is critical. Recent studies have demonstrated that NUSAP1 is highly expressed in various malignant tumors of the digestive system and plays a pivotal role in the initiation, progression, treatment, and prognosis of these tumors by regulating mitosis and key signaling pathways. The distinctive function of NUSAP1 positions it as a central molecule linking mitotic dysregulation with tumorigenesis, exhibiting dual potential as both a diagnostic marker and a therapeutic target. This article primarily reviews the structural characteristics, functional mechanisms, and related signaling pathways of NUSAP1, focusing on exploring the functional mechanisms of NUSAP1 in digestive system neoplasms. The objective is to offer new research perspectives into the diagnosis, treatment, and prognosis evaluation of tumors.